Synthesis and Structural Characterization of N-(4-Pyridyl)benzamide - Dong, Xiu-Yan; Wang, Li; Yang, Yu-Hua; Wang, Fa; Li, Yuan (Asian Journal of Chemistry, 2013)
Determination of the structure of N-(4-pyridyl)benzamide with the molecular formula C12H10N2O that the conformations of the N-H and C=O bonds are anti to each other, The -NH-C=O- group makes dihedral angles of 33.5(2)º and 17.1(2)º with the benzoyl and pyridyl rings, respectively, while the angle between the benzoyl and pyridine rings is 49.9(6)º. In the crystal structure, N-H···N hydrogen bonds link the molecules into a chain along the b axis. In addition, the structure is stabilized by p-p stacking interactions involving the benzene rings [centroid-to-centroid distance = 2.257(3) Å].